Diagnostic Dilemmas in Giant Cell Arteritis: Overcoming Anchoring Bias - Crystal Stewart; Rana H. Asif; Tahani Dakkak; Hardeep Singh; Muhammad Ali Javaid; Nikesh Patel (Case Reports in Rheumatology)
Giant cell arteritis (GCA), also known as temporal arteritis, is the most common systemic vasculitis in individuals over 50 and presents diagnostic challenges due to its nonspecific symptoms such as fever, headache, and fatigue. This case report describes the details of a male patient in his 70s who presented with recurrent intermittent fevers of unknown origin and was ultimately diagnosed with GCA after an extensive workup. His initial CT scans and lab tests were unremarkable. However, after a rheumatological workup displayed elevated erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels, along with new symptoms of ataxia and headaches, a temporal artery biopsy (TAB) was performed and confirmed the patient had GCA. This case underscores the difficulty in diagnosing GCA primarily due to physician anchoring bias, particularly when typical symptoms are not present. The case also showcases the need for increased awareness and prompt evaluation of potential GCA symptoms to prevent severe complications. Public education as well as improved hospital protocols can lead to earlier detection and treatment of GCA, reducing the risk of morbidity.